Marketing essentials - Farese, Lois Schneider (McGraw - Hill, 1997)
Marketing Essentials is the essential text for introducing students to the skills, strategies, and topics that make up the ever-changing world of marketing. It effectively captures the excitement of this fast-paced discipline with engrossing narrative, engaging graphics, and real-life case studies. This book is written in a very structured format. The repetitive structure of the lessons is classic and becomes easy to read after a couple of chapters. It includes interesting sidebars on people in not just marketing-related careers, but a wide range of product-related occupations, including enterpreneurs and business owners.